Application of Principal Component Proximity Transform and Geostatistics Methods for Volume Shale Distribution as Reservoir Characreristic Imaging in Seismic 3D - Islami, Nur (UI Scholars Hub, 2011)
Application of Principal Component Proximity Transform and Geostatistics Methods for Volume Shale Distribution as Reservoir Characreristic Imaging in Seismic 3D. Principal component proximity transform (PCPT) technique was used to predict the content of volume shale into seismic data in reservoir modeling framework. The goal in this research is to get the volume shale imaging in three dimensions and allow for reservoir modelling. The reservoir modelling requires an integrated quantitative and qualitative data sources collected separately, such as well and seismic data. Integrating PCPT and Geostatistic methods can generate the detail information for characterization of reservoir’s properties. Finally, it shows that the model was valid with correlation coefficient of 0.986 between volume shale in the well and predicted volume shale in the seismic. Reservoir zone can be found with low level of volume shale (